224 Risk Factors and Their Impact on Development and Severity of Allergic Diseases in the CIS-Region - Slavyanskaya, Tatiana (World Allergy Organization Journal, 2012)
BACKGROUND: This paper presents the results of influence of risk factors (RF) on development and severity of allergic diseases (ADs) in the CIS-region (CIS-R). METHODS: ISAAC and ARIA studies results, data on atopic dermatitis, Republic Ministries of Health Statistical Reports as well as literature data has been analyzed. RESULTS: It has been established that in industrialized areas, ADs is 2 to 3 times higher than the incidence in rural areas. The highest incidence is noted in ecologically unfavorable regions of low mountains where suffering from ADs is more often met. In the medium mountains ADs appear with less intensity, in conditions of high mountains ADs are extremely rare. The maximum prevalence of ADs has been observed at the experience of working in hazardous conditions from 5 years and above. A high degree of contamination airpollutions (CO2, NO2, SO2 etc.) in the industrial cities correlated with the prevalence of respiratory allergies and other ADs were observed. Frequent cause and significant allergens, as identified in patients with different ADs in CIS-R were domestic, epidermal, pollen and fungous allergens. The main triggers which involved in the development or exacerbation of ADs in Azerbaijan, Armenia, Russia and Uzbekistan are: house dust mites, pollen of trees and plants, pet allergens. In Belarus, Kazakhstan, Turkmenistan, Ukraine, Moldova, the cause-important allergens are: pollen of trees, grasses and weeds. Among the most significant risk F for ADs should be noted: burdened by heredity (65,5–75,9%), high frequency of SARS in history (16,2–77%), passive smoking (43,1–62,5%), poor social conditions (17–42%) the presence of pets in the apartment (12,5–17%). Children (7–8 years) were more susceptible to environmental RF as compared with teens (13–14 years). In Tajikistan and Turkmenistan, ADs were closely related with poor social conditions, low household income and large-family. CONCLUSIONS: Epidemiologic studies are of great theoretical and practical significance as they provide impartial evaluation and reliable data on ADs prevalence and the most important allergens. Climatic and geographical conditions of the environment and ecological situation in the region are significant RF, requiring consideration in determining the probability of a genetic predisposition to ADs.